Exposure to a Novel Insecticide Formulation on Maize and Concrete Reduces Movement by the Stored Product Pests, Prostephanus truncatus (Horn) and Sitophilus zeamais (Motschulsky) - Quellhorst, Hannah E.; Arthur, Frank H.; Bruce, Alexander; Zhu, Kun Yan; Morrison, William R. (Frontiers in Agronomy, 2022)
Two major stored products pests of maize are the Prostephanus truncatus Horn (larger grain borer) and Sitophilus zeamais Motschulsky (maize weevil). Under climate change, P. truncatus may be expected to shift its distribution northward further into the United States (US). Thus, there is a critical need to develop diversified chemical control tools in the post-harvest supply chain for these two species. In this study, we investigated the efficacy of a new reduced-risk insecticide Gravista®), containing the insect growth regulator, methoprene, combined with the pyrethroid, deltamethrin and the synergist piperonyl butoxide (Central Life Science, Schaumberg, IL, US), compared to the existing commercial standard formulation without synergist (Diacon IGR+®), and controls at inducing direct mortality and sublethal changes in movement on treated grains as a grain protectant, and on concrete as a surface treatment. Mortality of adults was assessed visually, while movement was tracked with a network camera coupled with Ethovision software that automatically recorded velocity and distance moved by both species, after continuous exposure on treated material for 4–168 h. The novel formulation significantly induced mortality while reducing distance and velocity moved by multiple-fold compared to controls for exposed adults even after relatively brief exposure periods. In fact, the novel formulation was just as effective as the older formulation, but used only a fraction of the active ingredients, thus it may be more cost-effective. Overall, the novel reduced-risk insecticide is a promising tool for controlling S. zeamais and P. truncatus in bulk storage and around other food facilities.